2018
DOI: 10.2147/ijn.s179159
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary impact of titanium dioxide nanorods: examination of nanorod-exposed rat lungs and human alveolar cells

Abstract: BackgroundTitanium dioxide nanoparticles have numerous applications, resulting in human exposure. Nonetheless, available toxicological and safety data are insufficient regarding aspherical particles, such as rod-shaped nanoparticles.MethodsIn a combined in vitro–in vivo approach, cultured A549 lung alveolar adenocarcinoma cells were treated with approximately 15×65 nm TiO2 nanorod-containing medium, while young adult rats received the same substance by intratracheal instillation for 28 days in 5 and 18 mg/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“… 41 TEM and DLS were performed both on freshly made suspension and after 3 months of storage at room temperature to prove suspension stability. Details of preparation of the TiO 2 NPs and the suspension, and the characteristics of them, were published by Horváth et al 15 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 41 TEM and DLS were performed both on freshly made suspension and after 3 months of storage at room temperature to prove suspension stability. Details of preparation of the TiO 2 NPs and the suspension, and the characteristics of them, were published by Horváth et al 15 …”
Section: Methodsmentioning
confidence: 99%
“…14 In one of our previous studies, rod-shaped TiO 2 NPs induced several inflammatory cytokines in the lungs of rats exposed to the nanorods subacutely via the airways. 15 The kidneys, exerting the function of removing xenobiotics, showed oxidative stress, increased inflammation markers, as well as functional and histological damages due to tubular necrosis in rats treated orally with (unspecified) nano-TiO 2 . 16 In another study, lipid peroxidation, reduced antioxidant activity, and proximal tubular apoptosis has been observed in the kidneys of rats after oral administration of spherical TiO 2 NPs of <100 nm in size for 3 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid direct use of UV radiation, NP surface modifications can be made, resulting in a shift in light absorption enabling the use of a different light source (Ni et al, 2017 ; Ziental et al, 2020 ). TiO 2 NPs have been the subject of a vast literature regarding their toxicity, sometimes polemical (Horváth et al, 2018 ; Suzuki et al, 2020 ), and their interaction with proteins impacting cell behavior (Jayaram et al, 2017 ; Runa et al, 2017 ).…”
Section: Nano-objectsmentioning
confidence: 99%
“…A comparison of P25 and food grade titania with TiO 2 -based bipyramids, rods and platelets indicated that only the food grade titania and platelets were genotoxic to human epithelial cells in vitro [ 32 ]. TiO 2 nanorods demonstrated a dose-dependent toxicity in alveolar adenocarcinoma cells in vitro but were not compared to differently shaped TiO 2 nanoparticles [ 33 ]. In the same study, the rats that inhaled the nanorods were found to exhibit tissue damage, acute and chronic lung inflammation, and increased levels of titanium were measured not only in lungs but also in the bloodstream.…”
Section: Introductionmentioning
confidence: 99%